Evaluation of The Spirulina (Arthrospira platensis Gomont) Antimicrobial Activity - Amor Bencheikh; Walid Mamache; Asma Gharzouli; Ahlem Kouachi; Haif Khadidja; Meriem Barkahoum Daichi; Noureddine Rouag (Turkish Journal of Agriculture: Food Science and Technology)
The present work was carried out to enhance biomass production of Spirulina (Arthrospira platensis Gomont) in a modified medium and to investigate “in vitro” its ability to produce antimicrobial substances against pathogenic bacteria and phytopathogenic fungi. The antibacterial activity was evaluated by the solid medium diffusion method on two pathogenic bacteria (Bacillus cereus & Klebsiella sp.), And the antifungal activity was evaluated on three phytopathogenic fungi (Alternaria solani, Cladosporium sp., Fusarium culmorum). The antibacterial test showed that the aqueous extract produced by S. platensis was more active against Gram-positive than on Gram-negative bacteria, the highest antibacterial activity was recorded against Bacillus cereus. Moreover, the Antifungal test showed that the aqueous extract was active against all three tested fungi and the highest antifungal activity was recorded against F. culmorum with over 90% inhibition of mycelial growth. The results of this research proved that cyanobacteria could be a good source for the production of antimicrobial agents which could be effective when compared with contemporary antimicrobial compounds and it can be used in the Biocontrol of several plant fungal diseases.